Ocean anatomy : the curious parts & pieces of the world under the sea - Rothman, Julia; Niekrasz, John (Storey Publishing, 2020)
"Follow Rothman's inquisitive mind and engaging artwork along shorelines, across the open ocean, and below the waves to explore the hows and whys of the watery universe, from how the world's oceans formed to why the sea is salty"--